1997
DOI: 10.1093/jac/40.6.855
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole versus nystatin in the prevention of candida infections in children and adolescents undergoing remission induction or consolidation chemotherapy for cancer

Abstract: An open, prospective, randomized pilot study was performed to assess the efficacy and safety of oral fluconazole 3 mg/kg once daily compared with oral nystatin 50,000 units/kg/day in four divided doses in preventing candida infections in 50 children undergoing remission induction or consolidation therapy for cancer. In 21 of 25 fluconazole-treated and 20 of 25 nystatin-treated patients the overall outcome of prophylaxis was clearly successful. Mild and transient oropharyngeal candidosis was observed in two and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…One study compared different routes of administration [17]. Seven of the 14 RCTs were exclusively conducted in neonates (term and preterm) [1723], while the remainder involved children across the paediatric age spectrum (birth–17 years) [2431]. Fluconazole was used as prophylaxis in six of the eight neonatal RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…One study compared different routes of administration [17]. Seven of the 14 RCTs were exclusively conducted in neonates (term and preterm) [1723], while the remainder involved children across the paediatric age spectrum (birth–17 years) [2431]. Fluconazole was used as prophylaxis in six of the eight neonatal RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…General measures for prevention of IA have been discussed in other chapters of this textbook and elsewhere [107]. Since there are no principal differences in this area between paediatric and adult patients, we will limit the discussion in this section to the current approaches to chemoprophylaxis in paediatric patients.…”
Section: Approaches To Preventionmentioning
confidence: 99%
“…A variety of different approaches have been explored in the past -mostly in adult patients with haematologic malignancies and/or allogeneic HSCT -without providing convincing preventative evidence for efficacy against IA [107][108][109]. Two recent large randomized clinical trials, however, have demonstrated that prophylactic posaconazole is effective in preventing IA in patients with acute myeloblastic leukaemia or myelodysplastic syndrome [110] and those with GVHD receiving augmented immunosuppressive therapy [111]; the first study also demonstrated a survival advantage in the posaconazole cohort.…”
Section: Primary Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…In kleinen vergleichenden Studien zeigte Nystatin geringere Effekte auf die orointestinalen Hefekolonisation als systemisch verabreichte Azole und war ineffektiv in der Prävention oberflächlicher bzw. invasiver Pilzinfektionen [52,60,159,170].…”
Section: Nicht-resorbierbare Orale Antimykotische Polyeneunclassified